Prophet Elijah as a Weather God in Church Slavonic Apocryphal Works - Enrique Santos Marinas (Religions, 2024)
The prophet Elijah took over the role of the Slavic pre-Christian god Perun as a weather god among the East and South Slavs in the period of syncretism just after the Christianization. We can find several examples of this in the twelfth-century Primary Chronicle or Tale of Bygone Years. However, unlike other characters from the Old Testament, Elijah was not honored with extensive translations of full apocryphal works, except for a group of Church Slavonic apocryphal fragments. Nonetheless, some original works devoted to the prophet Elijah were composed, such as the encomium attributed to St. Clement of Ohrid (9th–10th c.) or the Chants from the Orthodox Soul devoted to the Apocalyptic role of the prophet (15th c.). Along these lines, we will compare the latter with the extant apocryphal fragments in order to establish the possible influence of the apocryphal works, as well as identify original Slavic motifs that could date back to the pre-Christian period.